Screening tool for the identification of relative energy deficiency in Sport risk: validation of the low energy availability in female questionnaire - Italian version (LEAFQ-ITA) - Cinzia Ferraris; Lenycia de Cassya Lopes Neri; Anna Paola Amoroso; Francesca Bosio; Simona Fiorini; Monica Guglielmetti; Rossella Elena Nappi; Anna Tagliabue (Journal of the International Society of Sports Nutrition)
Background Relative Energy Deficiency in Sports (REDs) is defined as a multifactorial syndrome of impaired physiological and/or psychological functioning was previously named as the Female Athlete Triad. REDs was proposed to be an expansion of the Female Athlete Triad model (Triad), corresponding to a combination of Low Energy Availability (LEA), alteration of the menstrual cycle and bone health. could be made possible by a screening tool to determine the risk of LEA. The Low Energy Availability in Female-Questionnaire (LEAF-Q) is a screening tool originally developed to identify individuals at risk of Triad based on self-reported symptoms in three primary categories: injuries, gastrointestinal function, and reproductive function – to identify individuals at risk of Triad. To date, LEAF-Q is recommended in the International Olympic Committee REDs Clinical Assessment Tool-Version 2 as a screening tool for studying various health and performance outcomes of REDs. This study aims to validate the Italian version (LEAFQ-ITA) among physically active women while adapting it to their culture in order to enhance the diagnosis and facilitate access to treatment of REDs.Methods The validation process was carried out in multiple stages: (i) translation and cultural adaptation of the content from the original questionnaire (LEAF-Q) into the Italian culture; (ii) expert validation of the content using the Delphi technique; (iii) reliability test-retest in a sample of Italian physical active women; and (iv) internal consistency checking using exploratory and confirmatory factorial analysis. A consensus rate of more than 90% for every item was considered sufficient agreement. The test-retest reliability was evaluated using the intraclass correlation coefficient estimates and their 95% confidence intervals based on a mean-rating, absolute agreement, 2-way mixed-effects model. Exploratory and confirmatory factorial analyses were performed with the Factor software. The analysis was implemented using a matrix dispersion through Pearson correlations and the Robust Diagonally Weighted Least Squares (RDWLS) extraction method. The Parallel Analysis technique suggested the number of factors to be retained. McDonald’s Omega and Cronbach’s alpha were performed to test internal consistency.Results After two rounds, the LEAFQ-ITA maintained the same amount of items and gained the consensus of content validation specialists. From the sample of 215 questionnaires answered, a sub-sample of 105 participants answered the LEAFQ-ITA twice (mean age: 26.1 ± 4.7 years old; mean body mass index: 21.3 ± 2.6 kg/m2; physical activity of 3.9 ± 1.3 days/week on average). Among them, 56 women (37.6%) obtained a were classified at risk of LEA by the final score of LEAFQ-ITA ≥8. The single measurement intraclass correlation coefficient resulted in 0.832 (F = 10.849, df = 105, p < 0.000, 95% confidence interval: 0.762–0.882), which suggests high reliability. Although initially hypothesizing the presence of 3 factors, the parallel analysis suggested 2 factors as being the most representative of the data. Measures of McDonald’s Omega (0.65) and Cronbach’s alpha (0.64) suggested acceptable internal consistency.Conclusions The LEAFQ-ITA is a valid instrument for identifying Italian physically active women with physiological symptoms possibly related to LEA or REDs. Future research should focus on validating this instrument in other countries and languages.